2017
DOI: 10.3906/sag-1510-9
|View full text |Cite
|
Sign up to set email alerts
|

A prospective follow-up of quality of life, depression, andanxiety in children with lymphoma and solid tumors

Abstract: The aim of this study was the determination and prospective follow-up of quality of life, depression, and anxiety in pediatric patients with cancer under chemotherapy, as well as the evaluation of related factors.Materials and methods: Fifty newly diagnosed pediatric cancer patients and their parents were prospectively monitored before, during, and after therapy, and tests were used.Results: Significantly lower quality of life scores were recorded during treatment, in the group with CNS tumors, in the group re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(28 citation statements)
references
References 47 publications
(58 reference statements)
2
25
0
1
Order By: Relevance
“…It is our clinical experience that children and adolescents with brain tumors often feel anxious when confronted with the cognitive and academic challenges and that this anxiety is usually more severe in children with brain tumors compared to other tumors 18,19 . Our findings, regarding the association between the acute phase of treatment and the presence of anxiety disorders, are also in line with previous studies reporting that the acute phase of treatment, consisting of aversive side effects and uncertainty regarding the success of treatment, is anxiety‐provoking 11,14 …”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…It is our clinical experience that children and adolescents with brain tumors often feel anxious when confronted with the cognitive and academic challenges and that this anxiety is usually more severe in children with brain tumors compared to other tumors 18,19 . Our findings, regarding the association between the acute phase of treatment and the presence of anxiety disorders, are also in line with previous studies reporting that the acute phase of treatment, consisting of aversive side effects and uncertainty regarding the success of treatment, is anxiety‐provoking 11,14 …”
Section: Discussionsupporting
confidence: 92%
“…One study has shown that the levels of anxiety and depressive symptoms at 1 month after diagnosis predicted levels of anxiety and depressive symptoms at 1 year after diagnosis 8 . Furthermore, depression and anxiety scores were found to be significantly higher during the active medical treatment phase as compared to the period post treatment 11 …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Bu durum otonomi kazanılmasını zorlaştırabilir. [13][14][15][16] Özellikle ebeveynlerin ya da ergenin tanı öncesi duygusal problemleri varsa ya da problem çözme becerileri sınırlıysa ergenler daha çok risk altındadır. 17 Kanser ve tedavisine yönelik hastalık algısı, hastalıkla başa çıkma ve tedavinin zorluklarını göğüslemede etkili olmakta ve yaşam kalitesini doğrudan etkilemektedir.…”
Section: Introductionunclassified